Seasonal updraft speeds change cloud droplet number concentrations in low-level clouds over the western North Atlantic - Kirschler, Simon; Voigt, Christiane; Anderson, Bruce; Campos Braga, Ramon; Chen, Gao; Corral, Andrea F.; Crosbie, Ewan; Dadashazar, Hossein; Ferrare, Richard A.; Hahn, Valerian; Hendricks, Johannes; Kaufmann, Stefan; et al. (Atmospheric Chemistry and Physics, 2022)
To determine the impact of dynamic and aerosol processes on marine low clouds, we examine the seasonal impact of updraft speed w and cloud condensation nuclei concentration at 0.43 supersaturation n the cloud droplet number concentration (NC) of low level clouds over the western North Atlantic Ocean. Aerosol and cloud properties were measured with instruments on board the NASA LaRC Falcon HU25 during the ACTIVATE (Aerosol Cloud meTeorology Interactions oVer the western ATlantic Experiment) mission in summer (August) and winter (February March) 2020.